Flight Simulation and Technologies 1993
DOI: 10.2514/6.1993-3631
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of missile configurations with wrap-around fins using computational fluid dynamics

Abstract: AbsuactBackground

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 2 publications
3
9
0
Order By: Relevance
“…Previous CFD studies [9][10][11][12][13] of missile configurations with WAF have shown general agreement with experimental data of roll reversal, but always lacked accuracy in roll moment and side moment determination. Edge [11] considered both inviscid as well as viscous flows and calculated the roll moment using a three-dimensional full Navier-Strokes code.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…Previous CFD studies [9][10][11][12][13] of missile configurations with WAF have shown general agreement with experimental data of roll reversal, but always lacked accuracy in roll moment and side moment determination. Edge [11] considered both inviscid as well as viscous flows and calculated the roll moment using a three-dimensional full Navier-Strokes code.…”
Section: Introductionmentioning
confidence: 97%
“…Edge [11] considered both inviscid as well as viscous flows and calculated the roll moment using a three-dimensional full Navier-Strokes code. Abate and Cook [12] calculated the roll moment of WAFs attached to an infinitely long cylinder using Euler code. They pointed out that the accuracy of CFD greatly depends on the configuration modelled.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations